Large-deviation properties in some non-uniformly hyperbolic systems via Pesin theory. Issue 4 (1st October 2016) - Yin, Zheng; Chen, Ercai
ABSTRACT: This article is devoted to level-1 large-deviation properties in some non-uniformly hyperbolic systems via Pesin theory. In particular, our result can be applied to the diffeomorphisms on surfaces.